2022
DOI: 10.37284/eajab.5.1.998
|View full text |Cite
|
Sign up to set email alerts
|

Information Communication Technology Devices for Agricultural Information Dissemination among Smallholder Farmers in Uganda (Rubanda, Mayuge Districts, and Mbarara City)

Abstract: Agriculture continues to be the main source of livelihood in developing countries and smallholder farming is the most common type of agriculture practice supporting more than 70% of the population. On the other hand, information and communication technology (ICT) is quickly growing as its helping to connect easier and faster; thus, a dire need to harness it in promoting the agricultural sector. This study investigated the Information Communication Technology Devices for Agricultural Information Dissemination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Studies have further confirmed that ICTs stimulate cognitive and innovative behavior but also streamlines processes which fosters the ability to process and share more information for decision-making (Kravchenko, 2021;Munir and Beh, 2019;Harju et al, 2023;Hussain et al, 2023). In the agriculture sector, basic ICTs like mobile phones and televisions have bridged the information gaps created by the inaccessibility of extension workers and prevalent costs associated with reaching out to official government outreach centres (Byamukama et al, 2022;Subramanian, Bozzola and Nugent, 2022;Ravindra et al, 2020). While the benefits of using ICTs are vivid, acceptance maybe influenced by the perception an individual has about the complexity and usefulness of the said technology moderated by contextual variables like social influence (Ali et al, 2020;Gani et al, 2022;Li and Wang, 2022;Nyagango et al, 2023;Silva et al, 2023).…”
Section: Smallholder Maize Farmers In Ugandamentioning
confidence: 90%
See 2 more Smart Citations
“…Studies have further confirmed that ICTs stimulate cognitive and innovative behavior but also streamlines processes which fosters the ability to process and share more information for decision-making (Kravchenko, 2021;Munir and Beh, 2019;Harju et al, 2023;Hussain et al, 2023). In the agriculture sector, basic ICTs like mobile phones and televisions have bridged the information gaps created by the inaccessibility of extension workers and prevalent costs associated with reaching out to official government outreach centres (Byamukama et al, 2022;Subramanian, Bozzola and Nugent, 2022;Ravindra et al, 2020). While the benefits of using ICTs are vivid, acceptance maybe influenced by the perception an individual has about the complexity and usefulness of the said technology moderated by contextual variables like social influence (Ali et al, 2020;Gani et al, 2022;Li and Wang, 2022;Nyagango et al, 2023;Silva et al, 2023).…”
Section: Smallholder Maize Farmers In Ugandamentioning
confidence: 90%
“…The findings had several practical implications for managers and policymakers as they demonstrated that a combination of salient tools can boost information literacy levels among SHFs. Promoting information literacy requires adoption of tools like ICT, information culture and proper use of language in promoting information literacy (Munir and Beh, 2019; Byamukama et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation